2019
DOI: 10.1007/s10571-019-00772-7
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Trace Amines in the Brain-Gut-Microbiome Axis via Trace Amine-Associated Receptor-1 (TAAR1)

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 118 publications
0
19
0
Order By: Relevance
“…It has been shown that gut bacteria produce the neurotransmitter tyramine 49 . The highly increased level of its metabolite, tyramine-O-sulfate, in fecal samples of mice consuming HCl-acidified drinking water indicates altered tyramine synthesis and metabolism, which can affect gastrointestinal physiology and neurological function 50 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that gut bacteria produce the neurotransmitter tyramine 49 . The highly increased level of its metabolite, tyramine-O-sulfate, in fecal samples of mice consuming HCl-acidified drinking water indicates altered tyramine synthesis and metabolism, which can affect gastrointestinal physiology and neurological function 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Microbes are powerful in catabolizing AAs into a great variety of derivatives [ 39 , 40 ], many of which, including amines, nitric oxide (NO), indole, kynurenine, and quinolone, are neurologically active or affect human behavior through actions on the immune or endocrine system [ 41 , 42 ]. Key enzymes of AA-catabolism fall into three categories that participate in the decarboxylation, transamination, and deamination of AAs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we examined if Klamin ® induced relaxant effects via a direct action on the smooth muscle cells and/or via an indirect action involving neural pathways. Indeed, mouse and human studies reported that TAAR1 receptors are located in intestinal epithelial cells as well as enteric neurons of both submucosa and myenteric plexus [22,49,50].…”
Section: Discussionmentioning
confidence: 99%